Maximizing spectral sensitivity without compromising resolution in phase-incremented, steady-state solution NMR - Mark Shif; Yuval Zur; Adonis Lupulescu; Tian He; Elton T. Montrazi; Lucio Frydman (Nature Communications)
Abstract NMR acquisitions based on Ernst-angle excitations are widely used for maximizing spectral sensitivity without compromising bandwidth or resolution. However, if relaxation times T1, T2 are long and similar, as is often the case in liquids, steady-state free-precession (SSFP) experiments could provide higher sensitivity per $${\sqrt{\rm{acquisition}}_{\rm{time}}}$$ acquisition _ time (SNRt). Although strong offset dependencies and poor spectral resolutions have impeded SSFP’s analytical applications, this study reexplores if, when and how can phase-incremented (PI) SSFP schemes overcome these drawbacks. It is found that PI-SSFP can indeed provide a superior SNRt than Ernst-angle FT-NMR acquisitions, but that achieving this requires using relatively large flip angles. This, however, can restrict PI-SSFP’s spectral resolution and lead to distorted line shapes; to deal with this we introduce here a new SSFP outlook that overcomes this dichotomy. This outlook also leads to a new processing pipeline for PI-SSFP acquisitions, providing high spectral resolution even when utilizing relatively the large flip angles. The enhanced SNRt that the ensuing method can provide over FT-based NMR counterparts, is demonstrated with a series of 13C and 15N investigations on organic compounds.